EXPLORING THE BENEFITS OF PROJECT-BASED LEARNING IN CONTEMPORARY EFL SPEAKING INSTRUCTION - Wijaya, Kristian Florensio (Magister Scientiae, 2026)
The advent of innovative, creative, and interactive learning dynamics can promote better-facilitated speaking learning activities among EFL learners. These contextualized learning models are manifested with the employment of project-based learning, where language learners are commissioned to exert a more powerful control on their personalized communication practices. This small-scale library investigation aimed to delve more deeply into the advantages of project-based learning in modern EFL-speaking learning dynamics. Hence, the researcher employed a thematic analysis while analyzing the findings of 30 previous project-based learning studies to generate more systematic and comprehensible results. From the specifically generated findings, project-based learning helped provide real-time communication practices and promote emotionally supportive speaking classroom environments among EFL learners. Some recommendations were proposed to guide future research on the implementation of project-based learning in modern EFL-speaking contexts